TRANSFORMASI PENEGAKAN DISIPLIN PROFESI MEDIS: DARI MKDKI KE MAJELIS DISIPLIN PROFESI SEBAGAI SCREENING SYSTEM DUGAAN MALPRAKTIK - Gunawan Widjaja (JOURNAL OF COMMUNITY DEDICATION, 2025)
The transformation of medical professional discipline enforcement in Indonesia from the Indonesian Medical Disciplinary Council (MKDKI) to the Professional Disciplinary Council (MDP) marks a fundamental change in the system of supervision and resolution of alleged medical malpractice. This study aims to analyse these institutional changes and assess their implications for the effectiveness of the screening process for alleged malpractice. The research was conducted using a literature review method, drawing on legal literature, regulations, and the latest academic research related to the disciplinary enforcement system for healthcare professionals. The review findings indicate that the MDP expands the scope of oversight beyond doctors to include other healthcare professionals and strengthens the case screening mechanism before legal proceedings begin. This new system protects medical personnel from disproportionate criminalisation while ensuring patients' rights to adequate legal protection. Although it still faces implementation challenges such as institutional adaptation and the formulation of technical regulations, this transformation is considered capable of strengthening public trust in the national medical professional discipline system through more transparent, inclusive, and accountable governance.